A Theoretical and Empirical Reflection on Technology Acceptance Models for Autonomous Delivery Robots - Abrams, Anna M.H.; Dautzenberg, Pia S. C.; Jakobowsky, Carla; Ladwig, Stefan; Putten, Astrid M.Rosenthal-Von Der (2021 16th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2021)
In this work, we provide an argument and first empirical insights that existing technology acceptance models fall short when it comes to explaining spontaneous, unplanned and unsolicited encounters between humans and delivery robots on the street. Since technology acceptance models have been defined by the technology's perceived ease of use, perceived usefulness and behavioural intention to use, they are not well suited to explain acceptance in situations in which humans meet robots without any prior intention to use. Nevertheless, acceptance of delivery robots might be a driving force for safe navigation. Thus, the concept of acceptance should not be limited to its current focus on (planned) usage. In consequence, we i) expand the understanding of technology acceptance, ii) propose the concept of Existence Acceptance for autonomous systems, and iii) explore a new model for acceptance in an online study (n=185). Theoretical considerations hint towards the relevance of existence acceptance models for autonomous systems.CCS CONCEPTS*Human-centered computing \rightarrowUser models; User studies; Laboratory experiments; HCI theory, concepts and models; Empirical studies in HCI.